Trehalose, glycogen and ethanol metabolism in the gcr1 mutant of Saccharomyces cerevisiae - Seker, T; Hamamci, H (Folia microbiologica, 2003)
Since Gcr1p is pivotal in controlling the transcription of glycolytic enzymes and trehalose metabolism seems to be one of the control points of glycolysis, we examined trehalose and glycogen synthesis in response to 2% glucose pulse during batch growth in gcr1 (glucose regulation-1) mutant lacking fully functional glycolytic pathway and in the wild-type strain. An increase in both trehalose and glycogen stores was observed 1 and 2 h after the pulse followed by a steady decrease in both the wild-type and the gcr1 mutant. The accumulation was faster while the following degradation was slower in gcr1 cells compared to wild-type ones. Although there was no distinct glucose consumption in the mutant cells it seemed that the glucose repression mechanism is similar in gcr1 mutant and in wild-type strain at least with respect to trehalose and glycogen metabolism.
Keywords: Saccharomyces cerevisiae; Glycogen; regulace genové exprese u hub; DNA-Binding Proteins; ethanol; Ethanol; mutace; Saccharomyces cerevisiae Proteins; Saccharomyces cerevisiae - proteiny; Transcription Factors; fungální proteiny; Trehalose; trehalosa; transkripční faktory; glykogen; Fungal Proteins; Mutation; kultivační média; DNA vazebné proteiny; Gene Expression Regulation, Fungal; Culture Media